2020
DOI: 10.1021/acs.chemmater.0c03556
|View full text |Cite
|
Sign up to set email alerts
|

3D Bioprinted Highly Elastic Hybrid Constructs for Advanced Fibrocartilaginous Tissue Regeneration

Abstract: Advanced strategies to bioengineer a fibrocartilaginous tissue to restore the function of the meniscus are necessary. Currently, 3D bioprinting technologies have been employed to fabricate clinically relevant patient-specific complex constructs to address unmet clinical needs. In this study, a highly elastic hybrid construct for fibrocartilaginous regeneration is produced by coprinting a cell-laden gellan gum/fibrinogen (GG/FB) composite bioink together with a silk fibroin methacrylate (Sil-MA) bioink in an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 68 publications
1
50
0
Order By: Relevance
“…Interestingly, hybrid approaches have been explored showing promising achievements with respect to simultaneously addressing mechanical and biological functions. [ 87 ]…”
Section: Scaffolding Fabrication Methodsmentioning
confidence: 99%
“…Interestingly, hybrid approaches have been explored showing promising achievements with respect to simultaneously addressing mechanical and biological functions. [ 87 ]…”
Section: Scaffolding Fabrication Methodsmentioning
confidence: 99%
“…Three-dimensional (3D)-printed biomaterial constructs have been tried to generate different human tissues, including meniscus 10 - 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Romanazzo et al 137 mixed alginate with meniscal dECM (crosslinking by 48/92 mM CaCl 2 ). Other composite cell-laden bioink formulations were that reported by Sun et al, 136 using gelatin + fibrinogen + hyaluronic acid + glycerol incapsulating PLGA microparticles carrying TGFβ3 or CTGF; Jian et al, 135 combining GelMA with pig meniscal dECM (crosslinking by blue light, 405 nm); Costa et al, 139 proposing a sequential co-printing gellan gum/fibrinogen + porcine meniscus cells and SF methacrylate: here, gellan gum and fibrinogen lead to a stable hydrogel by a combination of ionic and enzymatic cross-linking while SF methacrylate lead to beta-sheet formation along culture time.…”
Section: Bioinks Formulations and Critical Issuesmentioning
confidence: 99%
“…According to our knowledge, only Costa et al 139 reported its use in a complex bioink formulation for 3D bioprinted meniscal scaffolds fabrication.…”
Section: Synthetic and Natural Materials For Meniscal Scaffolds Printing Conditioning And Bioprintingmentioning
confidence: 99%
See 1 more Smart Citation